2021
DOI: 10.1007/s00335-020-09856-y
|View full text |Cite
|
Sign up to set email alerts
|

The ring finger protein 213 gene (Rnf213) contributes to Rift Valley fever resistance in mice

Abstract: Rift Valley fever (RVF) is an emerging viral zoonosis that primarily affects ruminants and humans. We have previously shown that wild-derived MBT/Pas mice are highly susceptible to RVF virus and that part of this phenotype is controlled by a locus located on distal Chromosome 11. Using congenic strains, we narrowed down the critical interval to a 530 kb region containing five protein-coding genes among which Rnf213 emerged as a potential candidate. We generated Rnf213-deficient mice by CRISPR/CAS9 on the C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The discovery of RNF213 as a sensor for ISGylated proteins made us suspect that RNF213 could also have antiviral properties, similar to ISG15, which was in line with the recently reported increased susceptibility of Rnf213 -deficient mice to Rift Valley fever virus infection 62 . To investigate this, we infected cells with reduced or enhanced expression levels of RNF213 with different viruses.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The discovery of RNF213 as a sensor for ISGylated proteins made us suspect that RNF213 could also have antiviral properties, similar to ISG15, which was in line with the recently reported increased susceptibility of Rnf213 -deficient mice to Rift Valley fever virus infection 62 . To investigate this, we infected cells with reduced or enhanced expression levels of RNF213 with different viruses.…”
Section: Resultssupporting
confidence: 67%
“…Interestingly, while the protective effect of RNF213 against Listeria was dependent on ISG15, this was not the case for HSV-1, suggesting that different mechanisms underlie the antiviral and antibacterial effects. Of note, a recent study also uncovered that loss of RNF213 increases susceptibility to Rift Valley fever virus infection 62 , indicating that the antiviral activity of RNF213 extends beyond the viruses tested here.…”
Section: Discussionmentioning
confidence: 59%
“…First, Houzelstein et al reported a role for RNF213 in controlling Rift Valley fever infection in mice. These authors found that RNF213 KO animals were more susceptible to Rift Valley fever, hypothesizing this effect may be mediated by the role of RNF213 in lipid metabolism [71].…”
Section: Recent Discovery Of Rnf213 As a Key Antimicrobial Proteinmentioning
confidence: 98%
“…Metabolic functions of RNF213 include modulation of lipotoxicity [66], negative regulation of adipogenesis [65], and positive regulation of fat storage [57]. Immunerelated functions comprise the role of RNF213 in the response against infection [56,58,71], in antigen uptake and presentation [78], and in activation of the nuclear factor kappa B (NF-κB) pathway [66]. In addition, RNF213 is involved in WNT signaling [68] and hypoxia sensing [69,75].…”
Section: Recent Discovery Of Rnf213 As a Key Antimicrobial Proteinmentioning
confidence: 99%
“…Involvement of RNF213 in viral infection has just recently been reported. Homozygous deletion of Rnf213 showed significantly shorter survival in C57BL/6 J mice lethally infected with Rift Valley fever virus ( 90 ), an enveloped negative single stranded RNA viruses. The mechanism of entry is dynamin-dependent, CAV1-mediated endocytosis ( 91 ).…”
Section: Functions Of Rnf213 and Sgc In Vascular Insultsmentioning
confidence: 99%